2014
DOI: 10.1177/1524838014521321
|View full text |Cite
|
Sign up to set email alerts
|

Dating Violence Among College Students

Abstract: The research review synthesizes the knowledge base on risk and protective factors for dating violence while highlighting its relevance to violence against college women. In particular, the review highlights the personal, family, relationship, and behavioral factors that heighten the risk of dating violence victimization and perpetration while also noting the methodological limitations of the current body of empirical research and identifying directions for future academic work. Researchers have identified the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(76 citation statements)
references
References 88 publications
3
60
0
13
Order By: Relevance
“…Earlier evidence suggests that both of these factors may function as proximal markers for a more broad history of trauma: early traumatic experiences were found to predict dating violence in adolescence (Chiodo et al, 2012; Crawford and Wright, 2007; Kaukinen, 2014; Widom et al, 2014), and exposure to high-betrayal trauma in early life (e.g., traumatization by an important caregiver) is related to experiences of serious betrayal in adolescence or adulthood (Freyd, 1996; Hocking et al, 2016). The importance of broad trauma in early life is also supported by our findings for abuse and neglect, and by the very strong population-effect of traumatic experiences in general.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier evidence suggests that both of these factors may function as proximal markers for a more broad history of trauma: early traumatic experiences were found to predict dating violence in adolescence (Chiodo et al, 2012; Crawford and Wright, 2007; Kaukinen, 2014; Widom et al, 2014), and exposure to high-betrayal trauma in early life (e.g., traumatization by an important caregiver) is related to experiences of serious betrayal in adolescence or adulthood (Freyd, 1996; Hocking et al, 2016). The importance of broad trauma in early life is also supported by our findings for abuse and neglect, and by the very strong population-effect of traumatic experiences in general.…”
Section: Discussionmentioning
confidence: 99%
“…Although less research has been conducted on the link between alcohol use and dating violence among college-aged individuals, a growing body of literature suggests that there is a signifi cant association (Fossos et al, 2007;Hines & Straus, 2007;Rapoza & Baker, 2008;Stappenbeck & Fromme, 2010, 2014Stets & Henderson, 1991). A recent meta-analysis of dating violence perpetration among youth ages 11-21 concluded that the frequency or quantity of alcohol use, heavy episodic drinking (typically defi ned as consuming four or more drinks for women and fi ve or more drinks for men in a 2-hour period), and alcohol problems were positively associated with dating violence perpetration (Rothman et al, 2012a).…”
Section: Alcohol and Dating Violencementioning
confidence: 99%
“…This period typically corresponds with attendance in college, which has been shown to be a time of increased risk for dating violence (Kaukinen, 2014;Smith et al, 2003). Indeed, one in three college couples reported at least one incident of violence during their dating relationship (Jackson, 1999;Lewis & Fremouw, 2001).…”
mentioning
confidence: 99%
“…Exposure to dating violence in all forms during emerging adulthood is associated with a wide range of negative outcomes involving diminished relationship quality (Marcus, 2004) and individual adjustment, including low selfesteem (Katz, et al, 2000), substance use (Eshelman & Levendosky, 2012), school dropout (Kaukinen, 2014), and feelings of depression and anxiety (Hanson, 2002). To understand these negative outcomes in greater detail, researchers have often sought to explore the impact of specific types of dating violence (e.g., Ellis, Crooks, & Wolfe, 2009).…”
Section: Introductionmentioning
confidence: 99%